Investigating the Factors Impact the Decision to Invest in Rooftop Solar Power in Vietnam - Than, Duong Thuy Thi; Bui, Tuan Quang; Duong, Kien Trung; Tran, Trang Mai (International Journal of Energy Economics and Policy, 2022)
Renewable energy is one of the alternative solutions for today’s increasingly depleted energy sources. Solar energy and rooftop solar systems are new developments in many countries, including Vietnam. However, the investment in rooftop solar systems has not yet been implemented uniformly in Vietnam. This article uses the interview survey method by questionnaire to evaluate the factors affecting the investment in rooftop solar systems in some provinces in Vietnam. The research results show that most factors positively impact the intention to invest in rooftop solar systems. The authors will make some policy suggestions from the research results to increase investment in rooftop solar systems in Vietnam and towards environmentally sustainable development.